Validity and reliability of the Thai version of the confusion assessment method for the intensive care unit (CAM-ICU) - Tanyong Pipanmekaporn (2018)
Purpose: The purpose of this study was to determine the validity and reliability of the Thai version of the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU), when compared to the diagnoses made by delirium experts. Patients and methods: This was a cross-sectional study conducted in both surgical intensive care and subintensive care units in Thailand between February-June 2011. Seventy patients aged 60 years or older who had been admitted to the units were enrolled into the study within the first 48 hours of admission. Each patient was randomly assessed as to whether they had delirium by a nurse using the Thai version of the CAM-ICU algorithm (Thai CAM-ICU) or by a delirium expert using the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision. Results: The prevalence of delirium was found to be 18.6% (n=13) by the delirium experts. The sensitivity of the Thai CAM-ICU's algorithms was found to be 92.3% (95% confidence interval [CI] =64.0%-99.8%), while the specificity was 94.7% (95% CI =85.4%-98.9%). The instrument displayed good interrater reliability (Cohen's κ =0.81; 95% CI =0.64-0.99). The time taken to complete the Thai CAM-ICU was 1 minute (interquatile range, 1-2 minutes). Conclusion: The Thai CAM-ICU demonstrated good validity, reliability, and ease of use when diagnosing delirium in a surgical intensive care unit setting. The use of this diagnostic tool should be encouraged for daily, routine use, so as to promote the early detection of delirium and its rapid treatment. © 2014 Pipanmekaporn et al.